2011
DOI: 10.1007/s11524-010-9532-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-urban Differentials in the Utilization of Reproductive Healthcare in India, 1992–2006

Abstract: This paper examines trends in three reproductive healthcare indicators- namely, antenatal care, medical assistance at delivery, and contraceptive use among the urban poor and non-poor in India using data from the National Family Health Surveys, 1992-1993 and 2005-2006. The urban poor and non-poor are derived from composite wealth indices based on a set of economic proxies. Results indicate that the estimates of poor and non-poor are reliable. During the last 14 years, the service coverage in all three indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The pattern remained consistent across the selected background characteristics. The findings of this study are similar to that of the previous studies that revealed the enormous socioeconomic gap in health and health care utilization within urban settings [17], [24], [45], [46], [47], [48], [49]. Though the prevalence of childhood undernutrition was comparatively higher among the urban poor, the absolute higher prevalence among the urban non-poor children is also considerable.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The pattern remained consistent across the selected background characteristics. The findings of this study are similar to that of the previous studies that revealed the enormous socioeconomic gap in health and health care utilization within urban settings [17], [24], [45], [46], [47], [48], [49]. Though the prevalence of childhood undernutrition was comparatively higher among the urban poor, the absolute higher prevalence among the urban non-poor children is also considerable.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have examined the inequality in childhood undernutrition and found that the economic status of households is the prime contributor in explaining the inequality in childhood undernutrition in urban India [21], [22]. A few studies have also highlighted the growing poor/non-poor gap in the utilization of maternal healthcare services and child health in urban India [23], [24]. However, none of these studies explains the factors contributing to the gap in the utilization of the health services or child health between urban poor and non-poor.…”
Section: Introductionmentioning
confidence: 99%
“…A hospital-based study conducted in New Delhi showed that the use of contraceptives among urban poor was 52%, which is similar to contraceptive use in rural areas but below the use in well-educated urban populations (21). Data from the first and third round of the NFHS also showed that progress toward increased use of ANC and institutional delivery is occurring mainly among the urban non-poor, and that progress among urban-slum residents is slow (22). The burden of costs for maternal health care among the population living in slums is often significant.…”
Section: Resultsmentioning
confidence: 99%
“…Among illiterate women and women with primary education sterilization is the most common contraceptive method, while among women with high school education condoms were the most common (56). A study from New Delhi showed that illiterate women use contraceptives less compared to more educated women and when they do they prefer permanent methods of contraceptives (22). Level of education has also been shown to be associated with anemia, with less educated women being more likely to be anemic (57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation